Oxycodone vs. fentanyl in the treatment of early post-operative pain after total knee replacement: randomized controlled trial - Yang, Su-An; Kim, Keun-Sik; Kang, Hee Yong (Anesthesia and pain medicine (Korean society of anesthesiologists), 2016)
Background: Total knee replacement is often accompanied by severe post-operative pain. Oxycodone has sufficient analgesic effects and somewhat greater, but tolerable side effects compared to fentanyl. However, most studies on the topic evaluate visceral pain relief. In this study, we determine the effectiveness of oxycodone for somatic pain and evaluate the incidence of side effects. Methods: Sixty-nine patients were involved in a randomized control trial. Analgesic agents were administered to two experimental groups at a post anesthetic care unit (PACU) 15 min after PACU admission: a 50 g fentanyl group (n = 40) and a 4 mg oxycodone group (n = 29), both with severe pain (numeric rating scale, NRS ＞ 5). Changes in NRS at the PACU were measured. Additional analgesic agents were administered at 0–6, 6–12, 12–24, and 24–48 h after surgery. Results: Total fentanyl consumption and the number of patients who required additional opioids were significantly lower in the oxycodone group than in the fentanyl group. Incidence of side effects was not significantly different between the two groups. Conclusions: Oxycodone shows a better analgesic effect than fentanyl in somatic pain in the acute phase of post-operative pain. The side effects of oxycodone are not significantly different from those of fentanyl. KCI Citation Count: 0